THE CORRELATION BETWEEN SLEEP QUALITY AND MEMORY FUNCTION IN MEDICAL STUDENTS - Setyo Pambudi , Arif; Sahidu, Muhammad Ghalvan; Hunaifi, Ilsa (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Background: sleep is a physiological need for every human, including medical students. Studies have shown that poor sleep quality can lead to a decline in learning and memory abilities in medical students. The dual process theory explains that certain types of memory depend on common sleep conditions. This study aims to determine the association between sleep quality and short-term memory function, as measured by the digit span test, among medical students at the University of Mataram Objective: To determine the association between sleep quality and short-term memory function as measured by the digit span test among Medical Students at the University of Mataram. Methods: Observational analytic study with a cross-sectional design. The primary data included sociodemographic characteristics, Pittsburgh Sleep Quality Index, and the Digit Span Test. Data were analyzed using chi-square test and Fisher's exact test. Results: 62 participants were observed. Participants ranged from 18 to 23 years, with 42 students (67.7%) identified as female. 71% of the participants experienced poor sleep quality, while 29% reported good sleep quality. All 62 students showed normal performance in the forward digit span test. In the backward digit span test, 79% obtained normal results, while 21% performed abnormally. There is no relationship between sleep quality and short-term memory (p=0,739). Conclusion: sleep quality doesn’t influence memory function among medical students at the University of Mataram.